Kidney failure in children with Wilms tumor: A study based on urine analysis and ultrasound - Ali Ghasemi; Kazem Ghaffari; Alireza Gohari; Aziz Eghbali; Parsa Yousefichaijan; Vahid Falahati (Advanced Biomedical Research, 2022)
Background: Renal insufficiency is one of the inevitable complications in patients with Wilms tumor (WT). The purpose of this study was to assess the renal function in children with WT at baseline and every 3 months to 2 years. Materials and Methods: In a descriptive-analytical study from 2018 to 2020, 48 children with WT were included in the study. Urine creatinine (UCr), serum calcium (SCr), blood pressure (BP), estimated glomerular filtration rate (eGFR), and urinary protein (UPro) were evaluated at baseline and every 3 months during the study. Spot UCa/UCr and spot UPro/UCr ratio were calculated. Kidney ultrasonography was used in all patients. Independent Sample t-test and Chi-square tests were utilized to compare age and sex, respectively. Results: The mean age of patients at follow-up was 7.3 years. There was no significant difference in mean UCr, SCr, eGFR, 24-h UPro, UCa/UCr ratio, and spot UPro/UCr ratio at baseline and end of study (Pbaseline > 0.05, Pend of study > 0.05). Analysis of kidney size showed a statistical association with tumor stage (P < 0.05). Comparison of the kidney size in patients showed that there is a statistically significant difference (P < 0.0001) at baseline and end of the study. Conclusion: This study showed that as WT progressed, the size of the kidneys increases without any renal insufficiency. Therefore, it seems that urinalysis of patients with WT along with sonography is necessary to determine renal insufficiency and the use of ultrasound alone to determine kidney insufficiency is not recommended.